Perlindungan Konsumen Atas Pemblokiran Akun Akibat Pemberian Rating Satu pada Aplikasi Shopee Persepektif Hukum Islam dan Hukum Positif - Rizki Erlangga; Relit Nur Edi; Yusika Sumanto (Kartika: Jurnal Studi Keislaman, 2026)
The growth of e-commerce in Indonesia has made it easier for the public to conduct digital buying and selling transactions. A key feature of online marketplaces is the rating and review system, which serves as a means to evaluate product and service quality. However, in practice, a phenomenon has emerged where consumer accounts are blocked after assigning a one-star rating to specific products or services. This situation raises legal issues regarding the protection of consumer rights to express opinions and lodge complaints. This study aims to analyze the practice of account blocking resulting from one-star ratings on Shopee and to examine legal protections for consumers from the perspectives of both Islamic law and Indonesian positive law. The study employs a qualitative method with a normative-juridical approach, utilizing literature reviews and an analysis of various statutory regulations and Islamic legal sources. The findings indicate that unilateral account blocking without a clear reason potentially violates consumer rights as stipulated in Law Number 8 of 1999 concerning Consumer Protection. From an Islamic legal perspective, such actions contravene the principles of justice (al-'adl) and trustworthiness (amanah), as well as the maxim la dharar wa la dhirar (no harm and no reciprocating harm), which prohibits any act that causes detriment to others. Therefore, transparent and accountable mechanisms are required for the management of rating systems and account-blocking policies by marketplaces.